The relationship between probiotics and retinopathy of prematurity in preterm infants: A population-based retrospective study in China. - Bai, Wen Hua; Gu, Dan Feng; Dai, Yun; Chen, Yu Hong; Yang, Zu Ming; Lu, Li Jun (Frontiers in Pediatrics, 2023)
Background: Retinopathy of prematurity (ROP) is a retinal vascular disease with a high incidence in premature infants and is a leading cause of childhood blindness worldwide. The purpose of our study was to analyze the association between the use of probiotics and retinopathy of prematurity. Methods: This study retrospectively collected clinical data of premature infants with gestational age <32 weeks and birth weight <1500 g admitted to the neonatal intensive care unit from January 1, 2019 to December 31, 2021 in Suzhou Municipal Hospital, China. Demographic and clinical data of the inclusion population were collected. The outcome was the occurrence of ROP. The chi-square test was used to compare categorical variables, while the t-test and the nonparametric Mann-Whitney U rank-sum test were used for continuous variables. Univariate and multivariate logistic regression were used to analyze the relationship between probiotics and ROP. Results: A total of 443 preterm infants met the inclusion criteria, of which 264 didn’t receive probiotics and 179 were supplemented with probiotics. There were 121 newborns with ROP in the included population. The results of univariate analysis showed that the preterm infants with and without probiotics were significantly different in the gestational age, the birth weight, the one-minute Apgar score, the oxygen inhalation time, the acceptance rate of invasive mechanical ventilation, the prevalence of bronchopulmonary dysplasia, ROP and severe intraventricular hemorrhage and periventricular leukomalacia (P<0.05). Unadjusted univariate logistic regression model result showed that probiotics (OR 0.383, 95%CI 0.240~0.611) were the factors affecting ROP in preterm infants(P<0.01). Multivariate logistic regression result (OR 0.575, 95%CI 0.333~ 0.994) was consistent with univariate analysis (P<0.05). Conclusion: This study showed that probiotic was associated with a reduced risk of ROP in preterm infants with gestational age of <32 weeks and birth weight of <1500 g, but more large-scale prospective studies are still needed.